Crystal structure of (Z)-3-hydroxy-3-(4-methoxyphenyl)-1-(pyridin-2-yl)prop-2-en-1-one, C15H13NO3 - Radi Smaail (Zeitschrift für Kristallographie - New Crystal Structures, 2017)
C15H13NO3, monoclinic, Cc (No. 9), a = 3.9230(3) Å, b = 26.578(2) Å, c = 11.7147(12) Å, β = 94.028(8)°, V = 1218.4(2) Å3, Z = 4, Rgt(F) = 0.0387, wRref(F2) = 0.0877, T = 173 K.